Microneedling With Topical Insulin Versus Microneedling With Non-Cross-Linked Hyaluronic Acid for Atrophic Post-Acne Scars: A Split-Face Study - Shaimaa Hassan Mohamed; Ghada Abd-Elbadea Omar; Aliaa El-Sayed Hamdy (Mattioli1885, 2024)
Introduction: Post-acne scars are a prevalent cosmetic complaint that usually requires multi-modality treatment to achieve accepted results. Objectives: The target of this research was to evaluate and compare the efficacy and safety of microneedling with topical insulin against microneedling with non-cross-linked hyaluronic acid in atrophic post-acne scars treatment. Methods: The current comparative split-face research included 30 patients with atrophic facial acne scars. Each patient received 6 sessions of microneedling with topical insulin on one side of the face and microneedling with non-cross-linked hyaluronic acid on the other side. Sessions were done 3 weeks apart and digital photographs were taken before and 3 months after the last treatment session. Goodman and Baron qualitative and quantitative grading system was used to evaluate the improvement across both sides of the face, along with patient satisfaction. Results: After 3 months of the last session, a statistically significant improvement in qualitative acne scars grading on both sides of the face (p-value <0.001) was reported, with non-significant difference between the two sides (p-value =0.864). Moreover, the mean percentage of improvement in quantitative acne scars grading was 49.18 ± 13.22 on insulin side and 47.72 ± 15.08 on hyaluronic acid side, with non-significant difference between the two sides after treatment (p-value = 0.235). Conclusion: Both microneedling with topical insulin and with non-cross-linked hyaluronic acid have achieved comparable significant improvement of atrophic post-acne scars.